Learning Outcomes and Educational Effectiveness of Social Media as a Continuing Professional Development Intervention for Practicing Surgeons: A Systematic Review and Narrative Synthesis - Arashk Ghasroddashti, BSc; Fatimah Sorefan-Mangou, MB, BCh, BAO; Rosephine Del Fernandes, MSc; Erin Williams, MD, MSc; Ken Choi, MD; Boris Zevin, MD, PhD (Annals of Surgery Open)
Objective:. The objective of this systematic review was to assess the learning outcomes and educational effectiveness of social media as a continuing professional development intervention for surgeons in practice. Background:. Social media has the potential to improve global access to educational resources and collaborative networking. However, the learning outcomes and educational effectiveness of social media as a continuing professional development (CPD) intervention are yet to be summarized. Methods:. We searched MEDLINE and Embase databases from 1946 to 2022. We included studies that assessed the learning outcomes and educational effectiveness of social media as a CPD intervention for practicing surgeons. We excluded studies that were not original research, involved only trainees, did not evaluate educational effectiveness, or involved an in-person component. The 18-point Medical Education Research Study Quality Instrument (MERSQI) was used for quality appraisal. Learning outcomes were categorized according to Moore’s Expanded Outcomes Framework (MEOF). Results:. A total of 830 unique studies revealed 14 studies for inclusion. The mean MERSQI score of the included studies was 9.0 ± 0.8. In total, 3227 surgeons from 105 countries and various surgical specialties were included. Twelve studies (86%) evaluated surgeons’ satisfaction (MEOF level 2), 3 studies (21%) evaluated changes in self-reported declarative or procedural knowledge (MEOF levels 3A and 3B), 1 study (7%) evaluated changes in self-reported competence (MEOF level 4), and 5 studies (36%) evaluated changes in self-reported performance in practice (MEOF level 5). No studies evaluated changes in patient or community health (MEOF levels 6 and 7). Conclusions:. The use of social media as a CPD intervention among practicing surgeons is associated with improved self-reported declarative and procedural knowledge, self-reported competence, and self-reported performance in practice. Further research is required to assess whether social media use for CPD in surgeons is associated with improvements in higher level and objectively measured learning outcomes.